Stroking characteristics during time to exhaustion tests - Alberty, M.; Sidney, M.; Pelayo, P.; Toussaint, H. (Medicine & Science in Sports & Exercise, 2009)
Purpose: Race analyses during swimming reveal how exercise duration affects both clean swimming speed (v), stroke rate (SR), and stroke length (SL). The aim of this study is to provide an explanation for the change of SL and SR during paced exercise swimming the front crawl through an analysis of intracycle changes in motor organization.